Analisis pemanfaatan metaverse dalam perspektif industri kreatif dan sosial - Ayuni, Najmi Dinda; Juhana, Agus (LP2M Institut Teknologi dan Bisnis ASIA Malang, 2025)
The rapidly growing digital era has made the Metaverse concept a subject that must be developed within the creative industry and social activities. This article aims to examine how Metaverse is used from creative industry and social viewpoints. The method employed is a literature review, collecting information from a range of related sources. The Metaverse allows creators to produce and distribute their work in a safer, more transparent, and decentralized manner without third‑party involvement, unlike earlier models that required many intermediaries. It grants them greater control over their output and fairer royalty distribution. On the social side, Metaverse also creates interactive spaces where people can meet, interact, and collaborate in real time in ways never experienced before. This shapes how we build social relationships, cooperate in project‑based settings, and even attend events together virtually. Therefore, Metaverse can serve as a bridge between the physical and digital worlds that are becoming increasingly close, enabling individuals to merge within immersive virtual experiences.